Інформаційні технології моніторингу й управління бізнес-процесами притулку для собак - Штікель, А. Д. (ХНУРЕ, 2023)
This work is devoted to the information technologies in monitoring and control business processes of shelter for the dogs, full information about their health, features of care and contacts of their owners. This work provides data about current state of information system in the frame of reference, namely organization of shelters for the dogs and ways of improving existing solving and ways of optimizing business processes. Mentioned methods will help organization improve service, expand analyzing data of work efficiency, automate existing process and speed up operational processes